Pengaruh Bahasa Mandailing Terhadap Kemampuan Berbahasa Indonesia Mahasiswa Perantauan Di Kota Medan - Sari, Dewinta; Amalia, Diva; Padilah, Fany; Siregar, Hamidah Hanum (CV. ITTC INDONESIA, 2024)
This study aims to describe (1) the influence of Mandailing language interference with Indonesian in Indonesian language education study programs, (2) the factors causing language interference, and (3) comparison of Mandailing language interference and Indonesian language interference in Indonesian language education study programs. form of word, phrase and clause interference in sentences, the aim of this research is to discuss Mandailing language syntactic interference in students. This research is descriptive in nature, although it uses qualitative methodology. The regional language (mandailing) which is often used by students at Medan State University student, Faculty of Education, PG-Paud study program and surrounding areas uses Indonesian as the data format for this research.